Percutaneous Intervention for Quadrifurcation Lesion of the Left Main Coronary Artery - Murman, Kantaria; Vazha, Agladze; Pavle, Machavariani; Maka, Buleishvili; Mamuka, Kobalava; Nino, Otarishvili; Tamar, Sharashenidze; Ekaterine, Sagirashvili; Tamar, Sanikidze (Journal of Clinical Case Reports and Images, 2019)
To demonstrate that percutaneous coronary intervention (PCI) may in some cases be a safe option for patients with a high-risk surgical category, we report a complex clinical case of revascularization of multivessel coronary artery disease including left main coronary artery (LMCA) quadrifurcation. Methods For safety reasons, PCI was done in 2 separate sessions (staged PCI). Stenting of the LMCA quadrifurcation was performed using different stenting techniques in combination: modified balloon mini crush stenting technique was used - for LMCA and intermediate artery (IMA) stenting; modified balloon crush stenting technique was used for LMCA, circumflex artery (CX) and first obtuse marginal branch (OM1) stenting; provisional stenting technique was used for CX stenting, followed by sequential kissing balloon post-dilatation technique between LMCA and every branch; proximal optimization technique (POT) was performed in the LMCA. Left anterior descending artery (LAD), intermediate artery, circumflex artery, first obtuse marginal branch, left main coronary artery and its quadrifurcation were stented with 5 drug-eluting stents (DES) (Resolute Integrity, Medtronic); right coronary artery (RCA) was stented with 3 bare-metal stents (BMS) (Rebel, Boston Scientific). Results The interventions ended without complications, the ejection fraction increased from 35% to 48%, congestive heart failure functional class decreased to class I.  Subsequent coronary angiography, eight months after the last PCI, revealed patent stents with mild, nonsignificant restenosis. More than three years after the intervention, the patient has no complaints (according to MACE). Conclusions It should be considered that in case of the selection of suitable patients and the use of the appropriate revascularization technique, LMCA quadrifurcation lesion can be successfully treated with PCI.
Keywords: Percutaneous coronary intervention (PCI); Quadrifurcation of the Left Main Coronary Artery (LMCA); Coronary artery bypass grafting (CABG); Modified balloon crush stenting technique; Modified balloon mini crush stenting technique; Kissing balloon post-dilatation; Plain old balloon angioplasty.